Implementation of Pop-Up Learning Media to Increase Student Learning Motivation in MIN 1, Bengkulu City - Seli Nurhidayah; Melan Purtuna Sakti; Deni Febrini; Zubaidah Bayan; Ririn Selvianti (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2026)
Background: Although science learning in elementary schools has been a concern in several previous studies, studies specifically discussing the Project Based Learning learning model are still limited.method: This study uses a quantitative approach with a one-group pretest-posttest experimental design, involving 29 student participants/respondents selected based on purposive sampling techniques. Data were collected using test instruments, observation and documentation and analyzed using a paired sample t-test.Results: The results showed that the average pretest score of 65.66 increased to 81.86 in the posttest. The results of the statistical test showed that the t-count (-9.867) < t-table (-2.048) and a significance value of 0.01 < 0.05, so there is a significant influence between the Project Based Learning learning model on Science Learning Outcomes for Grade III.Conclusion: This study concludes that Project Based Learning plays an important role in improving Science learning outcomes and is recommended for implementation by teachers.